Influence of the surface roughness, lubrication and grinding on tribological properties of the c35 steel shot-peened surfaces - Martin Vicen; Otakar Bokůvka; Libor Trško; Richard Joch; Jozef Bronček; Ružica Nikolić; Robert Ulewicz (Applied Engineering Letters)
The roughness and lubrication of the contact surfaces play a major role in determining the contact forces and the coefficient of friction during contact between the two parts. The objective of the research, the results of which are presented in this paper, was to establish what, in fact, is the influence of those two important parameters on the surface properties of the shotpeened C35 steel specimens. Another important aspect that was considered was the influence of the post-treatment of the shot-peened specimen surfaces, the fine grinding. The experimental work included verification of the steel’s chemical composition (as compared to the standard values), the heat treatment, evaluation of the material’s microstructure, measurement of the mechanical properties, the shot-peening treatment and evaluation of the magnitude of the compressive residual stresses, measurement of the surface roughness profiles and the friction tests. An effect of the surface roughness and lubricant on the coefficient of friction (CoF) was established. The CoF values of the dry shot-peened steel surface after the fine grinding, as compared to the unground surface, decreased from about 30% to 39%. The application of lubricant caused the CoF to decrease by 66% and 43% for the ground and unground surfaces, respectively.